DESAIN DAN IMPLEMENTASI APD SERTA ALAT BANTU PENCEGAHAN VIRUS CORONA BAGI TENAGA KESEHATAN DI PUSKESMAS BUNGUS TELUK KABUNG PADANG - Derisma Derisma; Dodon Yendri; Lathifah Arief; M. Hafiz Hersyah; Ratna Aisuwarya; Rahmi Eka Putri; Rian Ferdian; Nefy Puteri Novani; M. Ridho Heranof; Yuni Anggraini (LPPM Universitas Andalas, 2020)
The community health centres, or commonly known as Puskesmas in Bahasa, are the backbone for Indonesia citizens in dealing with and fighting against the Covid-19 outbreak. They are the first responders and primary services that is closest to the community. Their healthcare professionals have a very important role as the front lines that identify the symptoms at the village level. It is mandatory that they use adequate personal protective equipment (PPE) when examining people's health. With the PPE, healthcare professionals remain protected from the risk of Covid-19 exposure. The lack of PPE availability sometimes makes many officers have to use any available materials as their protection. Addressing the lack of PPE availability in a Puskesmas of a suburban area like Bungus, the Department of Computer Systems, Universitas Andalas, decides to put some innovations into practice. In this community service activity, certain PPE and sterilization tool-aids are designed and developed to protect healthcare professionals from the risk of Covid-19 exposure. Some of the types of equipment provided for the centre are portable sterilization poles, hand sanitizer tool-aids that can be used without having to be touched by hands, face shield in the form of a face-covered hat using mica material that can be reused by washing or wiping it using a disinfectant, and hijack-masks made from spun-bond fabric that is comfortable and waterproof.